E-zakat fund accountability: Study on amil zakat institution Lazismu in Tokopedia - Shabrina Ramadania; Elvia Rosantina Shauki (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This study aims to explore and construct an accountability model for managing E-Zakat Funds in Lazismu for zakat funds collected online through Tokopedia. Methodology – This study applies a qualitative approach with a case study design. Interviews were used to collect the data with 7 (seven) informants, namely two from Lazismu, two from Tokopedia, and three informants from muzakki. Content, thematic, and constant comparative analyses were applied in this study.Findings – Exposed selves’ theory is very clear considering that no regulation applies this form of liability, thus creating limitations in claiming something beyond the supposed obligation. Opaque selves theory is also the reason that Tokopedia has not displayed the personal data of each muzaki for the e-zakat paid due to Tokopedia’s customer privacy. Decision Usefulness Theory, Tokopedia has fulfilled the needs according to the recipient criteria needed in this case, muzaki. Still, Tokopedia has not acted transparently regarding the distribution of funds in detail to the public and other stakeholders.Implications – This finding indicates the need for Amil Zakat Institutions (LAZ) management to pay special attention to e-zakat accountability. The results of this study offer an e-zakat accountability model that can be used by LAZ, which raises funds through the marketplace. Originality – There is still limited research that specifically examines the accountability of e-zakat funds.